Rise of empire eaudiobook - Sullivan, Michael J. (Riyria Revelations, 2012)
The adventure continues as Royce and Hadrian aid the struggling kingdom of Melengar as it alone stands in defiance against the newly formed empire. War approaches and a desperate gamble behind enemy lines is their only chance at forming an alliance with the Nationalists to the south. But Royce has plans of his own as he uses this opportunity to discover if an ancient wizard is using Riyria as pawns in his own bid for power. To find the truth, Royce must unravel Hadrian's hidden past. What he discovers will lead them to the end of the known world, on a journey rife with treachery and intrigue.